Measures for low back pain: a proposal for clinical use - Margareta Nordin; Neusa Maria Costa Alexandre; Marco Campello (Revista Latino-Americana de Enfermagem)
Low back pain represents a serious public health problem. Therefore, great efforts have been made in order to improve and assess the efficacy of its treatment. Reports in international literature have presented important studies concerning instruments to assess pain and functional incapacity in patients with low back pain. This study presents a clinical protocol which was developed by a multidisciplinary team. This protocol consists of the evaluation and distribution of pain, The Spitzer Quality of Life, The Oswestry Low Back Pain Disability Questionnaire, and The Center for Epidemiological Studies Depression Scale. Instruments must be urgently developed or adapted in order to be used according to the Brazilian reality.